Pendampingan dalam Pembentukan Karakter Keislaman Santri Taman Pendidikan Al-Qur’an (TPQ) Darusshalihin di Gampong Paya Bujok Tunong Kota Langsa, Propinsi Aceh - Masyhur, Laila Sari; Pratiwi, Siti Habsari; Ritonga, Mhd. Rasid (Saniya Institute, 2024)
This community dedication aims to strengthen the Koran Education Park's (Taman Pendidikan al-Qur'an) role in shaping the character of children in Paya Bujok Tunong, Langsa City. The environment occupies a significant and influential position in shaping the character of a child. Children often emulate their surroundings rather than following their parents' instructions. In an age of rapidly growing globalization, many things can shape a child's character. School isn't the only primary place for a child's character education. The educational park of the Qur'an plays a crucial role in shaping a child's character. These informal educational institutions also have a role in shaping the character of children. The results achieved in this community program of devotion show that (1) the presentation of the values of the Qur'an can shape the character of the child; (2) the praise of morality can affect the child's character; and (3) it motivates the child to take care of his environment according to Islamic values.